If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2h = 3h + 39 Reorder the terms: 4 + -2h = 39 + 3h Solving 4 + -2h = 39 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 4 + -2h + -3h = 39 + 3h + -3h Combine like terms: -2h + -3h = -5h 4 + -5h = 39 + 3h + -3h Combine like terms: 3h + -3h = 0 4 + -5h = 39 + 0 4 + -5h = 39 Add '-4' to each side of the equation. 4 + -4 + -5h = 39 + -4 Combine like terms: 4 + -4 = 0 0 + -5h = 39 + -4 -5h = 39 + -4 Combine like terms: 39 + -4 = 35 -5h = 35 Divide each side by '-5'. h = -7 Simplifying h = -7
| 26-3(2x+1)=11x-3(11+w) | | x-155=x | | X+(x-24)=200 | | 8y-5=19+5y | | 4c+8d-3c-5d= | | 4f+6+3(f-1)=3 | | 4x+42=85 | | (3x)(x^2+6)=3x^3+18x | | -8x-5y+9z=12 | | -40=4 | | 5x+10+20=8x-6 | | 3e-4=10-4e | | 2(3x-1)-4(x+2)=84 | | 8c+5=4c-12 | | (2z-3)(2+z)=z(2z-5) | | 0.8*x=27.15 | | -2(a+2)-6=-20 | | 9x+15-5x-7=60 | | 4t^3+3t^2+2t=0 | | x+x+v+v=w | | 2x+32=3x+93 | | f(x)=-6x+5 | | -4-x=-23 | | 3r+5=-r+17 | | 10x-2x=8 | | 10(x-3)=-25 | | 0.2*x=6 | | 5x-(5x+8)=12 | | 35x-5=7(5x+8) | | 0.4x-0.2(3-x)=.8 | | 3x+x+4=20 | | 20+3(x+8)=19-(3x-17) |